Abandoning or Reimagining a Cultural Heartland? Understanding and Responding to Rewilding Conflicts in Wales - the Case of the Cambrian Wildwood. (1st August 2018) - Wynne-Jones, Sophie; Strouts, Graham; Holmes, George
Abstract : This paper is about rewilding and the tensions it involves. Rewilding is a relatively novel approach to nature conservation, which seeks to be proactive and ambitious in the face of continuing environmental decline. Whilst definitions of rewilding place a strong emphasis on non-human agency, it is an inescapably human aspiration resulting in a range of social conflicts. The paper focuses on the case study of the Cambrian Wildwood project in Mid Wales (UK), evaluating the ways in which debate and strategic action to advance rewilding is proceeding, assessing the extent to which compromise and learning has occurred amongst advocates. As such, we provide an important addition to the field, by detailing how conflicts play out over time and how actors' positioning and approach shifts, and why. In this case, tempers have flared around the threat that rewilding is seen to pose to resident farming communities. Tensions discussed include the differing social constructions of landscape and nature involved; the distribution of impacts on different stakeholders; and the relative power of different actors to make decisions and gain representation. Responding to these, the paper outlines how rewilding advocates have sought to advance a more peopled and culturally responsive vision, which seeks to champion sustainable livelihood strategies. The changes in approach detailed demonstrate a reflexive stance from rewilders, which suggests that learning and adaptation can occur. Nonetheless, caution is expressed regarding the extent to which rewilding can truly advance inclusive opportunities for rural change, given a continued return amongst stakeholders to exclusionary narratives of belonging and authenticity, suggesting substantive difficulty in moving beyond longstanding concerns over identity and the re-imagination of place. Rewilding, it would seem, is about who we think we are and how we co-constitute our sense of self. We, therefore, close by arguing that tactics and politicking can only have so much bearing, tensions over rewilding are unavoidably emotional.